INNOVATIVE APPROACHES TO DEVELOPING DIGITAL CULTURE IN SOUTH KOREA - Khamitova, N. E.; Belyalova, A. E. (Journal of Oriental Studies, 2025)
The Republic of Korea is a world leader in digital technologies, and its innovative approaches actively influence the development of digital culture. This study aims to analyze innovative approaches to developing digital culture in South Korea and identify factors contributing to effectively implementing digital technologies in the cultural sphere. The main areas of the study include assessing the impact of technologies on cultural practices, analyzing public policies and strategies, and studying examples of successful integration of digital solutions into the cultural environment. The focus is on the relationship between digital innovations, cultural transformations, and their role in preserving cultural heritage and stimulating creativity. The scientific significance of the work lies in expanding the theoretical understanding of digital culture, and the practical significance is in developing recommendations for the effective implementation of digital technologies in the cultural sphere. The research methodology includes an integrated approach based on the analysis of documentary sources and statistical data to study innovative approaches to developing digital culture. The study also uses the game theory method and the network analysis method, which allows for a deeper understanding of the relationships between government organizations and cultural institutions. The study found that successful digitalization of South Korean culture depends on government support and collaboration between cultures and technologies. The findings could serve as a model for other countries seeking digital transformation in the cultural sphere. Keywords: digital culture, innovative approaches, South Korea, digital technologies